(untitled) (FIG Joint Land Administration Conference, 2025)
With the technological advancement of Unmanned Aerial Vehicle (UAV), new applications are being incorporated into municipal dynamics for territorial management. Uses such as monitoring irregular settlements and inspecting construction sites have become commonplace for bodies responsible for territorial management. However, the utility of UAVs for planning and cadastral updating purposes is increasingly significant. The multipurpose cadastre is the official record of a municipality’s land parcels, requiring periodic updates of parcel boundaries, primarily for fiscal purposes, to ensure fair tax collection. Given the growing interest in UAVs applications and the constant need for updated territorial information, this study conducts a systematic bibliometric review to better understand the relationship and contributions of UAVs to the qualification of the territorial cadastre. The Scopus database was used as the primary data source, and bibliometric analysis was performed using VOSviewer and Bibliometrix software. The search, conducted in April 2025, targeted documents until 2024. The bibliometric analysis of 140 results demonstrates a significant increase in publications over the last decade, with 2023 and 2024 having the highest number (18 and 22, respectively). China (21), Germany (13), the USA (10), the Netherlands (9), and Italy (9) were the most productive countries. A qualitative analysis of 13 key publications highlights the evolution from technical validation and accuracy comparisons with traditional methods towards practical applications in land rights registration, disaster response, tax inspection, and 3D cadastre. While most academic works recognize the relationship between UAV use and cadastral improvement, few delve into the challenges of integrating this data with pre-existing legal systems, the long-term sustainability of UAV-based programs, or the direct benefits for territorial governance and local populations.